Effects of fasting during Ramadan month on soccer-specific technical performance, cognitive function, and perceptions in soccer players - Elghoul, Y.; Ben Kahla, A.; Bahri, F.; Trabelsi, K.; Chtourou, H.; Frikha, M.; Aziz, A. R. (Journal of Sports Sciences, 2024)
We aimed to examine the effects of Ramadan fasting (RF) and high-intensity short-term maximal performance on elite soccer players` shooting accuracy, executive function (EF), and perceptions. Sixteen Muslim elite players fasting during Ramadan underwent assessments before (BR), during (DR), and after Ramadan (AR). Soccer-specific technical performance was evaluated using the Loughborough Soccer Shooting Test (LSST) before and after a 5-metre shuttle run test (5mSRT), conducted at the same time-of-day (17:00 h). Performance metrics recorded included higher distance (HD), total distance (TD), and fatigue index (FI). RPE after a 5-min warm-up and each repetition of the 5mSRT were obtained, and the mean RPE score was calculated. Trail Making Test (TMT Parts A and B) were used after the warm-up and the 5mSRT. Perceived difficulty (PD) was assessed following the LSST. HD, TD, and FI were not affected by RF (p > 0.05). DR, RPE and accuracy scores in the LSST were significantly lower after the 5mSRT compared to BR (1.29 vs. 1.24 AU; 1.29 vs. 1.24, respectively). In conclusion, RF had no adverse effects on physical performance. However, when combined with high-intensity running sessions, RF may impact accuracy and PD, and these adverse effects seem to have been translated into EF.